(3fWGb JWHjb GdbGfhf GdLfGFi ef MjK GdecGf habG ddeYWjGJ GdJcfhdhLjI (B/ s - (3YeQ YHjO eMeO GdZhds; (3GMeO YhV HdGd s; (3eGehf eMeO SdGeIs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2006)
(3JWHjb bGfhf GdYbhHGJ ef MjK GdecGf jSJhLH hLhO YdGbI eGHjf GdLQjeI hGdbGfhf GdhGLH GdJWHjb hgPg GdYdGbI GNPJ Tcd eHGOiA GSGSjI gi (B: (3eHOG GdGbdjejI hGdTNUjI hGdYjfjI hGdYGdejI hbO GNP GdbGfhf GdGeGQGJi hfXjQg GdaQfSi HgPg GdeHGOiA GdGQHYI hdcf GdbGfhf GdeUQi de jGNP HeHOG GdYdejIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2006s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B367-377s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3fXQjI ecGf GdaYd Gh GdLQjeIs; (3GdfJjLI GdGLQGejIs; (3eHOG GdGbdjejIs; (3GdLQGFe PGJ GdWHjYI GdNGUIs; (3GdLQjeI GdSHjIs; (3bGfhf GdYbhHGJ GdGeGQGJis; (3eHOG TNUjI GdbGfhf GdLfGFis; (3YjfjI GdfU GdLfGFis; (3eHOG YGdejI GdfU GdLfGFis; (3GdGfGHI GdbVGFjI GdOhdjI aj GdeSGFd GdLfGFjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs